Importancia de la pelvicefalometria en pacientes con sospecha de dcp y su relacion con la forma de terminación del parto. - Ortiz Consuegra, Mónica; Valenzuela, Ricardo (Revista Universidad de Guayaquil, 1997)
This study was conducted retrospectively on 78 patients who were admitted to the Enrique C. Sotomayor Gynecology and Obstetrics Hospital in labor and underwent radiographic pelvimetry accompanied by labor tests with a diagnostic impression of DCP. These were full-term pregnancies with cephalic presentation and independent of parity. Taking into account that the presence of DCP becomes evident only when one or more of the following changes occur: -Persistent delay in cervical dilation